Revision of the planthopper tribe Rhotanini (Hemiptera: Auchenorrhyncha: Derbidae) - Zelazny, B.; Webb, M. D. (Zootaxa, 2011)
Species of the tribe Rhotanini Muir (1918) (Hemiptera: Auchenorrhyncha: Derbidae) are found in the humid tropics of southern Asia, Australia, the Pacific and West Africa. In particular, many species are found in the rain forests of Borneo and New Guinea. This tribe has received little attention in the past and we provide a comprehensive taxonomic revision of its species. We recognize the following eight genera: Alara Distant, 1911 (=Mecynorhynchus Muir), 31 species, Dichotropis Muir, 1913, 9 species, Levu Kirkaldy, 1906, 34 species, Muiralevu Zelazny, 1981 (=Formolevu Yang & Wu, syn. nov.), 19 species, Rhotana Walker, 1857 (=Genestia Stål, = Decora Bierman), 72 species, Rhotanella Fennah, 1970, 8 species, Saccharodite Kirkaldy, 1907 (=Muiralyricen Metcalf, =Malpa Metcalf, = Genestiella Fennah), 108 species and Sumangala Distant, 1911, 13 species. Maps illustrating the distribution of these 8 genera and tables showing the distribution of each species are provided. A key to the genera is included. Where possible, species within each genus are grouped into species groups and keys are provided for the species within these groups. Keys are also given for the species of a genus found in a given country or larger island. The 116 previously known species of the tribe are reviewed and many are redescribed. We propose the following new combinations or new status: Rhotana biermani (Schmidt 1926) n. comb., Rhotana dammermani (Schmidt 1926) n. comb., Rhotana lalage (Fennah 1969) n. comb., Saccharodite palauensis (Fennah 1956) n. comb., Saccharodite ponapeana (Fennah 1956) n. comb., Levu haedulus (Fennah 1956) new status, Levu lactineus (Fennah 1956) new status, Levu paganus (Fennah 1956) new status, Muiralevu exotivus (Yang & Wu 1993) n. comb. and Muiralevu quadramaculatus (Muir) rev. comb. We also describe the following new species. For Alara: A. anulus Zelazny sp. nov., A. armifera Zelazny sp. nov., A. armilla Zelazny sp. nov., A. cheesmani Zelazny sp. nov., A. cultellus Zelazny sp. nov., A. frigida Zelazny sp. nov., A. lingua Zelazny sp. nov., A. linigera Zelazny sp. nov., A. rubicunda Zelazny sp. nov. and A. schmidti Zelazny sp. nov. from New Guinea and surrounding islands; A. aquilonia Zelazny sp. nov. and A. interrupta Zelazny sp. nov. from Laos; A. australiensis Zelazny sp. nov. from Australia; A. clava Zelazny sp. nov., A. cranstoni Zelazny sp. nov. and A. regia Zelazny sp. nov. from Borneo; as well as A. cornigera Zelazny sp. nov. from West Malaysia. For Dichotropis: D. brevis Zelazny sp. nov., D. flexuosa Zelazny sp. nov., D. maai Zelazny sp. nov., D. nivea Zelazny sp. nov., D. sedlacekorum Zelazny sp. nov. and D. sublimis Zelazny sp. nov. from New Guinea; D. peregrina Zelazny sp. nov. from New Guinea, Borneo and West Malaysia; as well as D. straatmani Zelazny sp. nov. from New Guinea and the Solomon Isl. For Levu: L. apiatus Zelazny sp. nov., L. candidus Zelazny sp. nov., L. echinus Zelazny sp. nov., L. elmohardyi Zelazny sp. nov., L. simplissimus Zelazny sp. nov., and L. triangularis Zelazny sp. nov. fromNew Guinea; L. apicalis Zelazny sp. nov. from Laos; L. confinis Zelazny sp. nov. from Vietnam; L. erraticus Zelazny sp. nov. from New Guinea and Vanuatu; L. immaculatus Zelazny sp. nov. and L. nocturnus Zelazny sp. nov. from Vanuatu; L. kirkaldyi Zelazny sp. nov., L. knighti Zelazny sp. nov., L. psittacus Zelazny sp. nov., L. pudens Zelazny sp. nov., L. rufigena Zelazny sp. nov. and L. shanahani Zelazny sp. nov. from the Solomon Isl.; as well as L. kraussi Zelazny sp. nov. from Tonga. For Muiralevu: M. cavernae Zelazny sp. nov., M. coniunctus Zelazny sp. nov., M. parvus Zelazny sp. nov., M. rufomarginatus Zelazny sp. nov. and M. silvestris Zelazny sp. nov. from Borneo; M. dimidius Zelazny sp. nov., M. ignavus Zelazny sp. nov., M. maestus Zelazny sp. nov., M. reticulatus Zelazny sp. nov., and M. telum Zelazny sp. nov. from West Malaysia; M. medleri Zelazny sp. nov. from Nigeria; M. septemspinosus Zelazny sp. nov. from the Ivory Coast and Nigeria; as well as M. vetus Zelazny sp. nov. from Java. For Rhotana: R. aequa Zelazny sp. nov., R. dentata Zelazny sp. nov., R. dextra Zelazny sp. nov., R. fordi Zelazny sp. nov., R. globosa Zelazny sp. nov., R. gracilis Zelazny sp. nov., R. luteola Zelazny sp. nov., R. melichari Zelazny sp. nov., R. novahiberniensis Zelazny sp. nov., R. panthera Zelazny sp. nov., R. papuensis Zelazny sp. nov., R. rubifasciata Zelazny sp. nov., R. sectator Zelazny sp. nov., R. similis Zelazny sp. nov., R. triplex Zelazny sp. nov. and R. unca Zelazny sp. nov. from New Guinea and neighbouring islands; R. aperta Zelazny sp. nov., R. crassa Zelazny sp. nov., R. cribraria Zelazny sp. nov., R. fera Zelazny sp. nov., R. hirashimai Zelazny sp. nov., R. holtmanni Zelazny sp. nov., R. kuncheriai Zelazny sp. nov., R. magna Zelazny sp. nov., R. pacata Zelazny sp. nov., R. reticulata Zelazny sp. nov., R. sabaea Zelazny sp. nov., R. suttoni Zelazny sp. nov. and R. truncata Zelazny sp. nov. from Borneo; R. argus Zelazny sp. nov., R. brendelli Zelazny sp. nov. and R. wallacei Zelazny sp. nov. from Sulawesi; R. deminuta Zelazny sp. nov. from New Caledonia; R. dohertyi Zelazny sp. nov. from India; R. gressittorum Zelazny sp. nov. and R. mendax Zelazny sp. nov. from Australia; R. jacobsoni Zelazny sp. nov. from Sumatra and West Malaysia; R. miles Zelazny sp. nov. from Borneo and the Philippines; R. ramosa Zelazny sp. nov. from Sumatra; R. spenceri Zelazny sp. nov. from Vietnam; R. stali Zelazny sp. nov. from Sri Lanka; as well as R. tridentata Zelazny sp. nov. from Borneo and West Malaysia. For Rhotanella: Rh. bipunctata Zelazny sp. nov. from Sulawesi; as well as Rh. cyclops Zelazny sp. nov. and Rh. sophiae Zelazny sp. nov. from New Guinea. For Saccharodite: Sa. abnormis Zelazny sp. nov., Sa. aculeata Zelazny sp. nov., Sa. affinis Zelazny sp. nov., Sa. aquila Zelazny sp. nov., Sa. aurora Zelazny sp. nov., Sa. bakeri Zelazny sp. nov., Sa. bos Zelazny sp. nov., Sa. carens Zelazny sp. nov., Sa. cervetta Zelazny sp. nov., Sa. colorata Zelazny sp. nov., Sa. costa Zelazny sp. nov., Sa. eburnea Zelazny sp. nov., Sa. foliata Zelazny sp. nov., Sa. hollowayi Zelazny sp. nov., Sa. ignea Zelazny sp. nov., Sa. lamina Zelazny sp. nov., Sa. lata Zelazny sp. nov., Sa. lucifera Zelazny sp. nov., Sa. lugubris Zelazny sp. nov., Sa. mappa Zelazny sp. nov., Sa. perlucida Zelazny sp. nov., Sa. plurima Zelazny sp. nov., Sa. propinqua Zelazny sp. nov., Sa. rufa Zelazny sp. nov., Sa. saucia Zelazny sp. nov., Sa. scissa Zelazny sp. nov., Sa. timida Zelazny sp. nov., Sa. tricuspis Zelazny sp. nov., and Sa. virgula Zelazny sp. nov. from Borneo; Sa. altissima Zelazny sp. nov., Sa. aucta Zelazny sp. nov., Sa. conducta Zelazny sp. nov., Sa. egregia Zelazny sp. nov., Sa. extraria Zelazny sp. nov., Sa. fasciata Zelazny sp. nov., Sa. media Zelazny sp. nov., Sa. minuscula Zelazny sp. nov., Sa. modesta Zelazny sp. nov., Sa. montana Zelazny sp. nov., Sa. nanus Zelazny sp. nov., Sa. nervosa Zelazny sp. nov., Sa. nigra Zelazny sp. nov., Sa. nishidai Zelazny sp. nov., Sa. picta Zelazny sp. nov., Sa. pirum Zelazny sp. nov., Sa. pulla Zelazny sp. nov., Sa. punctata Zelazny sp. nov., Sa. rosea Zelazny sp. nov., Sa. solitaria Zelazny sp. nov., and Sa. variabilis Zelazny sp. nov. from New Guinea and neighbouring islands; Sa. chinensis Zelazny sp. nov. from South China; Sa. crispa Zelazny sp. nov., Sa. gagnei Zelazny sp. nov., Sa. ligata Zelazny sp. nov. and Sa. teres Zelazny sp. nov. from New Caledonia; Sa. cruenta Zelazny sp. nov. from Borneo, Sumatra and Thailand; Sa. dionaea Zelazny sp. nov., Sa. insulana Zelazny sp. nov., Sa. obrieni Zelazny sp. nov., Sa. purpurea Zelazny sp. nov., and Sa. rubilineata Zelazny sp. nov. from the Solomon Islands; Sa. doddi Zelazny sp. nov. from Australia; Sa. indochinensis Zelazny sp. nov. from Laos; Sa. joycei Zelazny sp. nov. from Fiji; Sa. longuida Zelazny sp. nov. from West Malaysia; Sa. rostrata Zelazny sp. nov. from Borneo and Sumatra; Sa. satyrus Zelazny sp. nov. from Sumatra; Sa. securifera Zelazny sp. nov. from Borneo, Sumatra and West Malaysia; Sa. siamensis Zelazny sp. nov. from Thailand; Sa. vietnamensis Zelazny sp. nov. from Vietnam; Sa. viperina Zelazny sp. nov. from Borneo and West Malaysia; as well as Sa. vitrea Zelazny sp. nov. from New Guinea and the Solomon Islands. For Sumangala: Su. badia Zelazny sp. nov., Su. distanti Zelazny sp. nov., Su. nubila Zelazny sp. nov., and Su. tenebrosa Zelazny sp. nov., from Borneo; as well as Su. indica Zelazny sp. nov. from India. The brings the total species recognized in the tribe to 294. A neotype has been assigned for Genestia vitriceps Stål, 1858, now Rhotana vitriceps (Stål) and lectotypes have been designated for the following species: Alara dux Distant, 1911, Decora dammermani Schmidt, 1926 (now R. dammermani), Dichotropis amboinensis Muir, 1913, Levu africana Muir, 1926 (now M. africanus), L. amboinensis Muir, 1913, L. laratica Muir, 1913 (now Sa. laratica), L. matsumurae Muir, 1915 (now Sa. matsumurae), L. quadramaculata Muir, 1915 (now M. quadramaculatus), L. rubra Muir, 1913 (now Sa. rubra), L. samoensis Muir, 1927, L. vitiensis Kirkaldy, 1906, Mecynorhynchus fuscus Muir, 1915 (now A. fusca), Me. hyalinus Muir, 1915 (now Su. nigropunctata), Me. obscurus Muir, 1915 (now A. obscura), Rhotana albata Melichar, 1903, R. chrysonoe Kirkaldy, 1906 (now Sa. chrysonoe), R. formosana Matsumura, 1914, R. fuscofasciata Distant, 1906, R. haematoneura Kirkaldy, 1906, R. halosydne Kirkaldy, 1907 (now L. halosydne), R. kagoshimana Matsumura, 1914 (now Sa. kagoshimana), R. latipennis Walker, 1857, R. opalina Distant, 1907 (now Sa. chrysonoe), R. quadrimaculata Distant, 1907, R. ramentosa Distant, 1907, R. septemmaculata Distant, 1907, R. transversa Distant, 1907 (now Sa. chrysonoe), R. unimaculata Muir, 1914 (now R. maculata), R. venosa Distant, 1906, and Sumangala delicatula Distant, 1911.